Infection of juvenile falcons (Falco spp.) with intestinal Lawsonia intracellularis. Issue 2 (14th January 2023) - Wencel, Peter; Smith, Sionagh H; Couck, Liesbeth; Hellebuyck, Tom; Scott, Peter C; McOrist, Steven
Abstract: Intestinal infection of many host species with Lawsonia intracellularis are widely reported. Analyses of infections among carnivorous falcons have not previously been reported. Fifty juvenile captive falcons ( Falco spp.) with or without Lawsonia infection were investigated in the United Arab Emirates, including clinical laboratory methods. Fresh intestinal biopsy samples were analysed by microbiological techniques for Lawsonia and other bacteria and by standard parasitological and pathological methods. Lawsonia intracellularis infection was diagnosed by microbiological examination and qPCR in 10 of 50 juvenile falcons at case examination. Seven of these 10 falcons were of normal clinical appearance, and the other three had other contributing factors to ill‐thrift. A range of other conditions were noted in 40 case control falcons. This first report of Lawsonia infection in falcons suggests that the agent may have a limited contribution to clinical disease in these birds, including ill‐thrift syndromes. This lack of clinical disease association mimics that noted among Lawsonia infections recorded in other avian families.